ANALISIS STRATEGI PEMASARAN SYARIAH TERHADAP KEPERCAYAAN NASABAH DI BANK SYARIAH INDONESIA - Efriyanti, Novia; Fasa, Muhammad Iqbal (STAI Darul Qalam Tangerang, 2024)
Banks are an important financial institution in a country, because banks at macro and micro levels will be able to influence the economy. Sharia banks in Indonesian society are based on the wishes of various parties to provide financial transaction services whose activities are carried out based on Islamic sharia principles. According to sharia principles, marketing activities must be based on the spirit of worshiping God the Almighty Creator, making every effort possible for the common welfare, not for group interests, let alone personal interests. Research using qualitative research is research that depends on observations according to abilities that relate directly to the people around the research object. The researcher's aim is to analyze sharia marketing strategies on customer trust in Indonesian sharia banks. Researcher's Results Customer trust is an important asset for companies, maintaining loyal customers must be a greater priority than trying to get new customers